Nodulation bacteria, cucurbitacin-containing phytonematicides, dosage model and nutritional water productivity of sutherlandia frutescens in the context of climate-smart agriculture - Masenya, Tsobedu Absalom (My University, 2022)
The unique phytochemical composition of the medicinal plant cancer bush (Sutherlandia frutescens) have made its foliage to gain much attention in South Africa due to its health benefits. In situ harvesting of the plant parts of this important species serve as one potential strategy to avert its extinction through whole plant harvesting, a common practice by rural communities. However, such a strategy is limited by lack of information on the agronomic requirements of the plant species and its susceptibility to root-knot (Meloidogyne species) nematodes. The objectives of the study were four-fold, namely, to: (1) identify nodulation bacteria associated with wild S. frutescens using morphological and biochemical techniques, (2) assess the efficacy of the nodulation isolates from different centres of biodiversity of S. frutescens in Limpopo Province, South Africa (3) test the compatibility of cucurbitacin-containing phytonematicides on S. frutescens for managing population densities of Meloidogyne species and (4) determine the nutritional water productivity (NWP) of S. frutescens in association with water scarcity of the region where the plant species originated. In achieving Objective 1, nodules from S. frutescens roots were washed in distilled water and healthy, undamaged, firm and pink nodules were sterilised. Aseptic nodules from S. frutescens roots and commercial strains were transferred into a smasher biomerieux polythene bag containing 10 ml distilled water and crashed to produce a milky suspension the milky suspension was streaked on Yeast extract mannitol agar (YEMA). After gram reaction, colony characterisation includes the investigation of shape, colour, configuration, elevation and margin of bacterial colony as observed in colonies on nutrient agar plates of overnight grown microorganisms using a microscope. The medium for biochemical test was prepared, inoculated with 5 μl purified xxv bacterial cultures and incubated at 37°C for 48 h. Identification of the bacterial isolates was performed using VITEK 2 Systems (bioMérieux, Inc., North Carolina, USA). Using morphological and biochemical techniques, the bacterial species associated with roots of S. frutescens in the wild were assayed primarily those in the genera Raoutella ornithinolytica and Enterobacter cloacae species dissolvens. The VITEK 2 Systems confirmed the identification of the bacterial species from 80 to 96% of the samples. Three species were confirmed from another sampling area, Sphingomonas paucimobills, Raoutella ornithinolytica and Enterobacter cloacae species dissolvens from by 86 to 96% of the samples. In achieving Objective 2, the five treatments, namely, Bradyrhizobium spp. (Arachis) strain, Rhizobium leguminosarum strain, Tubatse strain, Sebayeng strain and untreated control, were laid-out in a randomised complete block design, with seven replications during the first season (Experiment 1) and with eight replications during the second season (Experiment 2). The seasonal interactions (Experiment 1 × Experiment 2) on plant and nutrient elements were not significant (P ≤ 0.05) and data for the two seasons were pooled (n = 75). Relative to untreated control, commercial (Bradyrhizobium and Rhizobium strain) and native strains (Tubatse and Sebayeng strain) significantly increased plant height by 31, 33, 44 and 40%, respectively, root length by 30, 41, 40 and 42%, respectively and dry shoot mass by 48,195 and 17%, respectively. Similarly, rhizobia strains significantly contributed to the increase in nitrogen assimilation by 7, 25 and 80%, respectively, protein synthesis by 13, 10, 24, 69%, respectively, and symbiotic efficiency by 31, 133, 292 and 82%, respectively. However, rhizobia inoculants had no significant effects on potassium and phosphorus in leaf tissues. In achieving Objective 3, in Mean Concentration Stimulation Point (MCSP) experiments, seven treatments, xxvi namely, 0, 2, 4, 8, 16, 32 and 64% for each phytonematicide, were arranged in a randomised complete block design (RCBD), with 8 replicates. In application interval experiments, treatments, based on “weeks-per-month-of-30 days” for M. javanica, which translated to 1, 2, 3 and 4 weeks, were arranged in a RCBD, with 10 replicates. Nemarioc-AL and Nemafric-BL phytonematicides had MCSP values of 3.43 and 4.03%, respectively, with the plant having high tolerance level to the products. The respective application interval of the two products for managing population densities of Meloidogyne species were 29 and 17 days. The dosage models for Nemarioc-AL and Nemafric-BL phytonematicides were 6.62 and 13.26%, respectively. In achieving Objective 5, the study used nine treatments designated as T1, T2, T3, T4, T5, T6, T7, T8 and T9, respectively, consisting of 1, 2, 3, 4, 5, 6, 7, 8 and 9 seedlings/hole of drip irrigation transplanted using a 3S planter under field conditions, arranged in randomised complete block design (RCBD) with 9 replications (n = 81) in two seasons. The NWP of total flavonoids, total tannin and total phenol exhibited positive quadratic relations in varied planting density suggesting that this cultural practices could be manipulated to improve NWP of cancer bush. In conclusion, the wild bacterial isolates, sampled from S. frutescens plant grown in the field, outperformed the commercial bacterial strains in enhancing the productivity of the test plants. The empirically established dosage model for Nemarioc-AL and Nemafric-BL phytonematicides could be used to control Meloidogyne species in cancer bush production. There is a need to further investigate the responses of the identified strains to the test phytonematicides. Findings of the study openend new frontiers in the development and commercialisation of the observed native bacterial strains for the cultivation of S. frutescens, which has excellent medicinal importance as a cure or management for cancer.
Thesis (Ph.D. Agriculture (Plant Production)) -- University of Limpopo, 2022
Keywords: Nodulation bacteria; Cucurbitacin; Phytonematicides; Medicinal plants -- South Africa; Root-knot nematodes; Medicinal plants -- Harvesting -- South Africa